All-solution processed inverted green quantum dot light-emitting diodes with concurrent high efficiency and long lifetime. Issue 10 (21st August 2019) - Yang, Zhiwen; Wu, Qianqian; Lin, Gongli; Zhou, Xiaochuan; Wu, Weijie; Yang, Xuyong; Zhang, Jianhua; Li, Wanwan
Abstract : An all-solution processed inverted green quantum dot-based light-emitting diode with concurrent high efficiency and long lifetime is obtained by precisely controlled double shell growth of quantum dots. Abstract : All-solution processed inverted quantum dot light-emitting diodes (QLEDs) are promising candidates for lighting and display applications. While the external quantum efficiency of inverted devices is comparable to that of devices with normal structure, achieving both high efficiency and long lifetime in such inverted devices remains challenging. Herein, we report an all-solution processed inverted green QLED capable of achieving a 96.42 cd A −1 current efficiency, a 25.04% external quantum efficiency, and a 4943.6 h half-lifetime. This external quantum efficiency exceeds reported literature values, and the lifetime is over 19 times greater than those of previously reported all-solution processed inverted QLEDs. Such excellent performance is attributed to the precisely controlled double ZnS shells of CdSeZnS/ZnS/ZnS quantum dots, which can effectively suppress Auger recombination and Förster resonance energy transfer, as well as decrease efficiency roll-off at high driving currents. Overall, this study suggests that shell engineering of quantum dots may provide an effective means of accelerating the inverted QLEDs to meet requirements for practical display and lighting applications.